Sistem Pendukung Keputusan Seleksi Bantuan Siswa Miskin Menerapkan Kombinasi Metode SAW dan ROC - Andri Yunaldi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Decision support system (DSS) is a system that helps decision makers in this case the principal, so that the decisions produced are considered effective and appropriate to solve the problems faced. Specifically in determining the provision of assistance to poor students, the determination of the criteria is aimed at making the recipient of the assistance in accordance with the purpose of the assistance itself. In this study, the authors applied a combination of SAW and ROC methods in selecting beneficiaries. ROC (Rank Order Centroid) is a method that can produce weight values, while Simple Additive Weighting (SAW) is a method used to rank poor prospective student assistance recipients as an alternative. The results of the study are expected to contribute to the development of science, especially the principal in the selection decision for recipients of poor student assistance